Simulation for Generation of Several Types of Pulses in an Yb-Doped Mode-Locked Fiber Laser - Youshuo Cui; Jinrong Tian; Zikai Dong; Runqin Xu; Zexin Zhang; Yanrong Song (IEEE Photonics Journal, 2020)
We numerically demonstrated six types of pulses in an Yb-doped fiber laser, including dissipative soliton (DS), dissipative soliton resonance (DSR), multipulse, noise-like pulse (NLP), breathing soliton and soliton explosion. The influence of cavity conditions on DSR pulse properties is discussed systematically. It is found that the change of the saturation power of saturable absorber (SA) could transform DSR into various types of pulses. Saturation power of SA and injected signal affect the number and shape of multipulse. Furthermore, the influence of the saturation power of SA and intra-cavity dispersion on pulse type is diagrammed intuitively. By properly adjusting the transmission curve of SA, breathing soliton and soliton explosion can be obtained as well.